Parabolic Trough Solar Collector Initial Trials - Pikra, Ghalya; Salim, Agus; Purwanto, Andri Joko; Eddy, Zaidan (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2011)
This paper discusses initial trials of parabolic trough solar collector (PTSC) in Bandung. PTSC model consists of concentrator, absorber and tracking system. Concentrator designs are made with 2m aperture width, 6m length and 0.75m focal distance. The design is equipped with an automatic tracking system which is driven using 12V and 24Watt DC motor with 0.0125rpm rotational speed. Absorber/receiver is designed with evacuated tube type, with 1 inch core diameter and tube made of AISI304 and coated with black oxide, the outer tube is borosilicate glass with a 70 mm diameter and 1.5 m length. Working fluid stored in single type of thermal storage tank, a single phase with 37.7 liter volume. PTSC model testing carried out for 2 hours and 10 minutes produces heat output and input of 11.5 kW and 0.64 kW respectively.Â